The origin and course of the infrapatellar branch of the saphenous nerve: An anatomical study. (December 2022) - Krijgh, David D.; List, Emile B.; Teunis, Teun; Bleys, Ronald L.A.W.; Coert, J. Henk
Summary: Nerve injury of the saphenous nerve or infrapatellar branch seems to be a frequent complication following knee surgery or trauma. Denervation results vary, and in some cases, no pain relief is achieved. This might be due to anatomic variation. The purpose of this anatomical study is to identify the variation in the course of the infrapatellar branch and saphenous nerve. We dissected 18 cadavers from adult donors. Medial to the knee, the saphenous nerve and infrapatellar branch were identified and followed proximally to the point where the infrapatellar branch branched from the saphenous nerve. The location where the infrapatellar branch came off from the saphenous nerve relative to the knee joint and where it passed the knee joint were measured. A total of 23 infrapatellar branches were found. We identified 10 branches between 0–10 cm proximal to the knee joint, 3 branches at 10–20 cm, and 9 branches at >20 cm. Between the patella and semitendinosus tendon, the knee joint was crossed by 5 branches in the anterior, 15 in the middle, and 2 in the posterior one-third. The origin of the infrapatellar branch and the location at which it passes the knee are highly variable. This, in addition to people having multiple branches, might explain why denervation is frequently unsuccessful. Based on the anatomical findings, we propose a more proximal diagnostic nerve block to help differentiate between a distal-middle or proximal origin of the infrapatellar branch. Appropriate placement of the nerve block might help identify people who benefit from denervation.